The fecal microbiota of healthy donor horses and geriatric recipients undergoing fecal microbial transplantation for the treatment of diarrhea - McKinney, Caroline A.; Oliveira, Bruno C.M. [UNESP]; Bedenice, Daniela; Paradis, Mary-Rose; Mazan, Melissa; Sage, Sophie; Sanchez, Alfredo; Widmer, Giovanni (My University, 2020)
Background and aims Fecal microbial transplantation (FMT), a treatment for certain gastrointestinal conditions associated with dysbiosis in people, is also empirically employed in horses with colitis. This study used microbiota high-throughput sequencing to compare the fecal microbial profile of healthy horses to that of geriatric microbial transplant recipients experiencing diarrhea and tested whether FMT restores microbiota diversity. Methods To evaluate the effect of environment and donor characteristics on the intestinal microbiota, fecal samples were collected per rectum from 15 healthy young-adult (2–12 years) and 15 geriatric (≥20 years) horses. Additionally, FMT was performed for 3 consecutive days in 5 geriatric horses with diarrhea using feces from the same healthy donor. Fecal samples were collected from both donor and recipient prior to each FMT and from recipients 24 hours following the last FMT. The profile of the fecal bacterial microbiota was compared using 16S amplicon sequencing. Results and conclusions In contrast to diet and farm location, age did not significantly affect the healthy equine fecal microbiota, indicating that both healthy geriatric and young-adult horses may serve as FMT donors. The fecal microbiota of horses with diarrhea was significantly more variable in terms of β-diversity than that of healthy horses. An inverse correlation between diarrhea score and relative abundance of Verrucomicrobia was identified in surviving FMT recipients. At study completion, the fecal microbiota of horses which responded to FMT had a higher α-diversity than prior to treatment and was phylogenetically more similar to that of the donor.